A DESCRIPTIVE ANALYSIS OF BRAZIL: THE IMPORTANCE OF TOURIST ENTERTAINMENT - Rodrigues, Francisca Lucielia Justino (Seven Editora, 2024)
Tourist entertainment plays a crucial role in the economic and social development of Brazil’s tourist regions. This study investigated the importance of tourist entertainment in the Brazilian context, describing its various forms, economic benefits, contribution to the diversification of the regional economy, infrastructure strategies and professional training, relationship with environmental preservation, involvement of the local community, use of technology and the challenges faced by the sector. In addition, the study aimed to propose strategies and recommendations to promote the sustainable development of tourist entertainment in Brazil. The results highlight the need for investments in infrastructure, professional training and environmental awareness, as well as the use of technologies to improve the tourist experience. Collaboration between the public and private sector, together with the active participation of the local community, is essential for the success of tourism entertainment and for the achievement of the country’s sustainable development goals. DOI: https://doi.org/10.56238/sevened2024.037-111